First record of Capnobotrys dingleyae (Metacapnodiaceae) on Taxus baccata for southern Europe. (2nd November 2017) - Karadelev, M.; Rusevska, K.; Venturella, G.; Torta, L.; Gargano, M. L.
Abstract: Field investigations carried out in a mixed forest of Fagus sylvatica and Taxus baccata in the Nebrodi Natural Park (Sicily, southern Italy) allowed us to identify a very rare lignicolous ascomycete Capnobotrys dingleyae, a new species for southern Europe.